Post-synthesis strategy to integrate porphyrinic metal–organic frameworks with CuS NPs for synergistic enhanced photo-therapy. Issue 5 (8th January 2020) - Hu, Xiaochun; Lu, Yonglin; Zhou, Lulu; Chen, Lv; Yao, Tianming; Liang, Shujing; Han, Junyi; Dong, Chunyan; Shi, Shuo
Abstract : A multi-functional nanoplatform (PCN-CuS-FA-ICG) for combined photodynamic and photothermal therapy was presented, which demonstrated good inhibition of tumor growth. Abstract : Multifunctional nanotheranostic systems with both therapeutic and imaging functions are highly desired for the development of more effective and less toxic anti-tumor drugs. Herein, a simple but effective method is reported to fabricate a novel PCN-CuS-FA-ICG-based nanoplatform for dual-modal imaging-guided synergistic photothermal/photodynamic therapy. Porphyrinic metal–organic frameworks with CuS NPs are obtained in aqueous solution via a simple post-synthesis strategy. Furthermore, to obtain a more effective therapy, indocyanine green (ICG) was incorporated into the multifunctional theranostic platform to promote the photothermal therapeutic effect. The as-prepared PCN-CuS-FA-ICG not only exhibits an excellent 1 O2 generation efficiency under 650 nm irradiation to achieve remarkable photodynamic cell killing, but also presents outstanding photothermal conversion under 808 nm irradiation to destroy tumor tissues by hyperthermia. In particular, the nanotherapeutic agent realized fluorescence and thermal imaging dual-modal imaging-guided cancer treatment. Meanwhile, in vivo experiments confirmed the evident accumulation of nanoparticles (NPs) at local tumors, and tumor growth was inhibited obviously via synergistic photothermal/photodynamic therapy with negligible side effects.